A test of lens opacity as an indicator of preclinical Alzheimer Disease. (November 2015) - Bei, Ling; Shui, Ying-Bo; Bai, Fang; Nelson, Suzanne K.; Van Stavern, Gregory P.; Beebe, David C.
Abstract: Previous studies reported that characteristic lens opacities were present in Alzheimer Disease (AD) patients postmortem. We therefore determined whether cataract grade or lens opacity is related to the risk of Alzheimer dementia in participants who have biomarkers that predict a high risk of developing the disease. AD biomarker status was determined by positron emission tomography-Pittsburgh compound B (PET-PiB) imaging and cerebrospinal fluid (CSF) levels of Aβ42 . Cognitively normal participants with a clinical dementia rating of zero (CDR = 0; N = 40) or with slight evidence of dementia (CDR = 0.5; N = 2) were recruited from longitudinal studies of memory and aging at the Washington University Knight Alzheimer's Disease Research Center. The age, sex, race, cataract type and cataract grade of all participants were recorded and an objective measure of lens light scattering was obtained for each eye using a Scheimpflug camera. Twenty-seven participants had no biomarkers of Alzheimer dementia and were CDR = 0. Fifteen participants had biomarkers indicating increased risk of AD, two of which were CDR = 0.5. Participants who were biomarker positive were older than those who were biomarker negative. Biomarker positive participants had more advanced cataracts and increased cortical light scattering, none of which reached statistical significance after adjustment for age. We conclude that cataract grade or lens opacity is unlikely to provide a non-invasive measure of the risk of developing Alzheimer dementia.